Continuity or Discontinuity, Revisiting the Legacy of Wali Sanga Mosques: Case studies of Contemporary Mosques of Nahdliyin in Malang, East Java - Putrie, Yulia Eka; Martokusumo, Widjaja; Budi, Bambang Setia (Nakhara : Journal of Environmental Design and Planning, 2017)
Many mosques in East Java are built by the Nahdliyin and are culturally affiliated to Nahdlatul Ulama (NU), the biggest Indonesian moderate Muslim organization. NU maintains a specific value system as the continuation of the Wali Sanga tradition. This paper discusses the representation of these values and traditions in the contemporary mosques of Nahdliyin in Malang, East Java. These mosques are where a great basis of the Nahdliyin experiences dynamic interaction with other Muslim groups take place. The results show that despite their pluralistic formal expressions, these contemporary mosques of Nahdliyin share similar values and traditions with Wali Sanga mosques.